PENGARUH ALOKASI BELANJA RUTIN DAN BELANJA MODAL PADA INDEKS PEMBANGUNAN MANUSIA - Astia Dewi, I G A Agung; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2016)
Human Development Index (HDI) is an indicator that can be used measuring the welfare. The aim of this study is determine the effect of the allocation recurrent expenditure and capital expenditure on HDI at District/City Province Bali. This study uses quantitative approach using a form of associative and secondary data obtained through collecting data with non behavioral observation method form study documentation. D ata of this study have passed the classic assumptions test and the suitability of the model test with Adjusted R 2 value is 17.3%. The research data was processed using multiple linear regression analysis technique. The analysis showed that recurrent expenditure significantly and positive impact on the HDI while capital expenditure no significantly and negative impactt on the HDI. The failure of the capital expenditure affect HDI because in addition to the low amount of capital expenditures allocated in improving the welfare of society and the allocation of capital expenditures have not been implemented on target.
Keywords: recurrent expenditure, capital expenditure, human development index